PERAN SERTA MASYARAKAT DALAM TERTIB BERLALU LINTAS (STUDI KASUS DI KEPOLISIAN RESOR SINTANG) - Sugianto - (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2022)
This study are focus on the awareness of people toward traffic rules at sintang regency. This study designed as a form of juridical sociological approach. The study are intended to recite the regulation and the fact of the awareness of people to obey traffic rules.The sample of research are the chief of police resort of sintang regency, the chief of Transportation Development Division, the transportation agency, 2 road user as perpertrators of traffic violations, 2 road user as the victiom of traffic violations. The result prove that there were lack of awareness to obey the traffic rule. it means the roads user needs to know the true regulation as mentioned on number 22 of 2009 about traffic rules and transportation. This study provide several suggestion, namely: the stakeholder needs to socialize the traffic rules broadly as regulated in mumber 22 of 2009 broadly, The road user needs to know better traffic sign, the stakeholders need explicitnes to enforce law, and every road user must obey the traffic rules.Keywords:Violation,Trafficandtransportationdevelopment